GENEVA SECURITIES CONVENTION AND RUSSIAN CIVIL LEGISLATION REFORM: COMPARATIVE PERSPECTIVES - M. Botvinov (BRICS Law Journal)
The Russian Parliament has modified the Civil Code recently. This reform has also covered the regime of uncertificated securities. Under the modified Civil Code (RCC) uncertificated securities do not constitute chattels but claims and other rights against the issuer. The legislator has also precised such issues as the methods of transfer and the creation of an interest upon those securities (Art. 149.2 of the RCC), the protection of the titleholder including the rights of a bona fide purchaser (Art. 149.3 of the RCC) and the liability of an intermediary resulting from the loss of the records (Art. 149.5 of the RCC).In 2008, in Switzerland, the Parliament has adopted the Federal Intermediated Securities Act (FISA). The present Act has introduced a new object to the Swiss legal order: an intermediated security. The intermediated securities are distinguished from those in paper form and from the immobilized securities. The Swiss delegation has participated actively in the preparatory works that resulted later in the adoption of the UNIDROIT Convention on Substantive Rules for Intermediated Securities, also known as Geneva Securities Convention. However, this Convention has not been ratified by Switzerland.The author analyzes the key issues of the reform in relation to uncertificated securities. We examine in particular whether the provisions governing the regime of uncertificated securities under the modified Civil Code of the Russian Federation have become more compatible with Geneva Securities Convention. Finally, we will try to explain why this Convention is not in force and whether the Russian Federation and Switzerland could ratify it.